Kajian Omzet UMKM Kota Padang Saat Pandemi Covid 19 Ditinjau Dari Faktor Internal dan Eksternal - Yenni Del Rosa; Idwar Idwar (Universitas Dharma Andalas, 2021)
The research objective was to examine the turnover of UMKM in the city of Padang during the Covid 19 pandemic in terms of various internal and external factors. The research method uses an associative method with a quantitative approach. The study population was 371 UMKM and a sample of 193 UMKM were taken by purposive sampling. Data collection techniques with field research, interviews, observation and questionnaires. Before the data is processed, the instrument test and classical assumption are tested on all research variables. It turns out that all these assumptions can be fulfilled. The result of multiple linear regression Y = 7.982.1 + 8.13X1 + 3.58X2 + 1.37 X3 - 6.41X4 - 7.52X5 + 2.73X6 - 5.26X7 + e. Hypothesis testing partially and simultaneously was carried out at a significance level of 5%. The test results of accountability, business climate and access have a significant negative effect on MSME turnover, while the variables of capital, human resources, law and infrastructure have a significant positive effect on MSME turnover in the city of Padang. Correlation of all internal and external factors with the turnover of MSMEs in the city of Padang is R = 0.534 and R2 = 0.286 and Adjusted R square = 0.238. ABSTRAK Tujuan penelitian mengkaji omset UMKM kota Padang saat pandemi covid 19 ditinjau dari berbagai faktor internal dan faktor eksternal. Metode penelitian memakai metode asosiatif dengan pendekatan kuantitatif. Populasi penelitian 371 UMKM dan sampel 193 UMKM diambil secara purposive sampling. Teknik pengumpulan data dengan field research, wawancara, observasi dan angket. Sebelum data diolah terlebih dahulu dilakukan uji instrumen dan uji asumsi klasik terhadap semua variabel penelitian ternyata semua asumsi tersebut dapat dipenuhi. Hasil regresi linier berganda Y = 7.982.1 + 8.13X1 + 3.58X2 + 1.37 X3 - 6.41X4 – 7.52X5 + 2.73X6 – 5.26X7 + e. Uji hipotesis secara parsial dan simultan dilakukan pada tingkat signifikansi 5%. Hasil ujinya akuntabilitas, ikim usaha dan akses berpengaruh negatif signifikan terhadap omset UMKM sedangkan variable modal, sumberdaya manusia, hukum dan infrastruktur berpengaruh positif signifikan terhadap omset UMKM kota Padang. Korelasi semua faktor internal dan eksternal dengan omset UMKM kota Padang nilai R = 0.534 dan R2 = 0.286 serta Adjusted R square = 0.238.